Одержання та дослідження покриттів на основі тугоплавких сполук хрому з підвищеними фізико-механічними та експлуатаційними властивостями I. Електрофоретичні покриття на основі CrS₂ i Cr₃C₂ - Медюх, В.К.; Кудь, І.В.; Уварова, І.В.; Медюх, Р.М. (Вісник Українського матеріалознавчого товариства, 2017)
The production technology of electrophoretic coatings on the base of refractory chrome compounds obtaining by the methods of high and low temperature synthesis of pre-mechanically activated reaction mixtures has been investigated. The influence of technological parameters and powder dispersion on the effectiveness of the deposition, structure and coatings morphology was examined. The reasonability of the strengthening heat-treatment of electrophoretic coatings has been shown.